P164 Changing patterns of the use of lung biopsy in interstitial lung disease. (15th November 2016) - Brockbank, L; Hilal, E; Holemans, J; Greenwood, J; Walshaw, M; Mohan, K
Abstract : Introduction: Radiological and international guidelines have improved the diagnosis of interstitial lung disease (ILD) subtype in the absence of a surgical lung biopsy (SBx). However, it may still be needed since up to 38% of cases 1 cannot be diagnosed on clinical and radiological grounds alone, and new antifibrotic therapies require more diagnostic certainty for idiopathic pulmonary fibrosis (IPF). We wished to ascertain whether SBx rates and diagnostic outcomes had changed at our regional thoracic centre. Methods: We looked at 104 consecutive patients undergoing SBx between May 2014 to April 2016, and compared their mode of referral and outcome with a previous study (210 cases) in the same centre conducted between 2001 and 2008. Results: There was no evidence of multidisciplinary team (MDT) input prior to SBx in 31 cases (30%), but 18 (17%) were discussed at an ILD MDT and 55 (53%) in local radiology meetings. For SBx outcome see Table. Prior diagnosis was uncertain in 28% of ILD MDT cases and 27% of local radiology meeting cases, whereas SBx confirmed the suspected diagnosis in 22% of ILD MDT cases but only 9% of radiology meeting cases. Conclusion: Overall, there appears to be increase in the ILD cases referred for SBx. Despite the small proportion of cases discussed at the ILD MDT prior to SBx, there appears to be a trend in the reduction of UIP/NSIP and significant increase in HSP, RBILD and DIP cases. Histological diagnosis remains important in ILD, and the use of other techniques with lower complication rates (e.g. transbronchial cryobiopsy) needs to be established. Reference: Raghu G, Mageto YN, Lockhart D, et al . The accuracy of the clinical diagnosis of new-onset idiopathic pulmonary fibrosis and other interstitial lung disease. A prospective study. Chest 1999;116 :1168–1174.